Eksplorasi Praktik Nilai-Nilai Kepemimpinan Asta Brata di Kabupaten Buleleng - Ni Luh Putu Risna Cahyani; Redan Werang, Basilius; Ketut Desia Tristiantari, Ni (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2024)
This study aims to explore the implementation of Asta Brata leadership values ​​by Elementary School Principals in Buleleng Regency, Bali. Asta Brata, derived from Hindu philosophy, emphasizes eight guiding principles that are in harmony with nature to create effective leadership practices. Using a qualitative case study approach, this study investigated the values ​​upheld by school leaders through interviews with thirteen Principals from two educational clusters. Key findings revealed four main themes: Professional Ethics, Responsibility, Harmony, and Example. In particular, Professional Ethics emerged as the most widely practiced value, emphasizing fairness and accountability in leadership. These insights underscore the relevance of local cultural values ​​in shaping effective school leadership, contributing to improved educational outcomes and fostering community support for school initiatives.